My son, the time traveler - Greenburg, Dan.; Davis, Jack E. (New York : Grosset & Dunlap, 1997)
When Zack goes to a store to buy a baseball card, he finds himself face-to-face with his future son who has traveled back in time.
Keywords: Time travel; Supernatural